Community engagement in the development of bioenergy projects from cellulosic urban waste feedstock in Hawaii for sustainable aviation fuel - Rush, Leslie; Simonpietri, Joelle; Kukac, Naomi (Frontiers in Sustainable Cities, 2025)
The purpose of the research project was to reveal the perceptions of residents and communities of the City and County of Honolulu concerning bioenergy projects, feedstock, and sustainable aviation fuel. The perception study was conducted via community-scale surveys, interviews, and town meetings to gather feedback on the preliminary design of a proposed bioenergy project, including feedstock choice and the need for sustainable aviation fuel in Hawaii. Residents on the west side of Oahu were targeted due to their proximity to the proposed plant site location. Findings from this study aim to identify resident perceptions, understanding, and desire for bioenergy projects and new infrastructure to, improve the energy efficiency and sustainability of Hawaiian islands. While Hawaii has created policies and mandates to move towards 100% renewable energy sources by 2045, the focus has been predominately on renewable electricity, largely overlooking other sustainable energy options such as sustainable aviation fuel. There is a lack of research on the community engagement and perceptions of Hawaiian residents on bioenergy projects and sustainable aviation fuel, contributing to the low adoption of bioenergy projects on the islands. Insights from this study aim to add literature on the need for community engagement in the design process, the importance of accepting new sustainable infrastructure, and the production and use of sustainable aviation fuels.